Organic iron at ultralow doses catalyzes hydrogen peroxide to eliminate cyanobacterial blooms: a study on algicidal effects and mechanisms under natural conditions - Lin, Yongdong; Niu, Ziru; Li, Juan; Li, Sijin; Li, Hai; Li, Lei (Frontiers in Environmental Engineering, 2025)
Hydrogen peroxide (H2O2) is gaining recognition as an eco-friendly and highly effective algicide for combating cyanobacterial blooms. This study investigates the algicidal potential of H2O2 catalyzed by both inorganic and organic iron. Our findings indicate that inorganic iron (FeSO4) shows minimal catalytic activity on H2O2 under varying light conditions. In contrast, organic iron, specifically the combination of H2O2, EDTANaFe, and light irradiation, demonstrates significant algicidal effects. The optimal dosages were identified as 10 mg/L for H2O2 and 3 mg/L for Fe3+.The limited efficacy of inorganic iron stems from the transformation of Fe2+ to Fe3+ ions via the Fenton reaction. Under neutral conditions, Fe3+ ions precipitate as large-sized goethite, which adheres to the extracellular polymeric substances (EPS) of cyanobacterial cells, thereby hindering H2O2 catalysis and hydroxyl radical (·OH) formation in natural waters. Conversely, the combination of light radiation and organic iron salts greatly enhances the algicidal efficiency of H2O2. This synergy accelerates H2O2 decomposition and facilitates the production of a substantial amount of OH radicals by altering the Gibbs free energy. Thus, bright and sunny conditions, particularly in the afternoon, are crucial for effectively combating cyanobacterial blooms using Fenton-like reagents. The methodology presented in this study offers a viable solution to global cyanobacteria bloom issues and elucidates the mechanisms driving its efficacy.